Β-Adrenergic induced SR Ca2 + leak is mediated by an Epac-NOS pathway. (July 2017) - Pereira, Laëtitia; Bare, Dan J.; Galice, Samuel; Shannon, Thomas R.; Bers, Donald M.
Abstract: Cardiac β-adrenergic receptors (β-AR) and Ca 2 + -Calmodulin dependent protein kinase (CaMKII) regulate both physiological and pathophysiological Ca 2 + signaling. Elevated diastolic Ca 2 + leak from the sarcoplasmic reticulum (SR) contributes to contractile dysfunction in heart failure and to arrhythmogenesis. β-AR activation is known to increase SR Ca 2 + leak via CaMKII-dependent phosphorylation of the ryanodine receptor. Two independent and reportedly parallel pathways have been implicated in this β-AR-CaMKII cascade, one involving exchange protein directly activated by cAMP (Epac2) and another involving nitric oxide synthase 1 (NOS1). Here we tested whether Epac and NOS function in a single series pathway to increase β-AR induced and CaMKII-dependent SR Ca 2 + leak. Leak was measured as both Ca 2 + spark frequency and tetracaine-induced shifts in SR Ca 2 +, in mouse and rabbit ventricular myocytes. Direct Epac activation by 8-CPT (8-(4-chlorophenylthio)-2′- O -methyl-cAMP) mimicked β-AR-induced SR Ca 2 + leak, and both were blocked by NOS inhibition. The same was true for myocyte CaMKII activation (assessed via a FRET-based reporter) and ryanodine receptor phosphorylation. Inhibitor and phosphorylation studies also implicated phosphoinositide 3-kinase (PI3K) and protein kinase B (Akt) downstream of Epac and above NOS activation in this pathway. We conclude that these two independently characterized parallel pathways function mainly via a single series arrangement (β-AR-cAMP-Epac-PI3K-Akt-NOS1-CaMKII) to mediate increased SR Ca 2 + leak. Thus, for β-AR activation the cAMP-PKA branch effects inotropy and lusitropy (by effects on Ca 2 + current and SR Ca 2 + -ATPase), this cAMP-Epac-NOS pathway increases pathological diastolic SR Ca 2 +  leak. This pathway distinction may allow novel SR Ca 2 + leak therapeutic targeting in treatment of arrhythmias in heart failure that spare the inotropic and lusitropic effects of the PKA branch. Graphical abstract: Highlights: Beta-adrenergic receptors (B-AR) induce arrhythmogenic SR Ca leak in adult rabbit and mouse ventricular myocytes. Previously proposed parallel pathways involving Epac or NOS signals are actually in series. This SR Ca leak is via a B1AR-cAMP-Epac2-PI3K-Akt-NOS1-CaMKIIδ-RyR2 phosphorylation cascade. This parallels B-AR/cAMP inotropic and lusitropic PKA effects on Ca current and SR Ca uptake.